2023
DOI: 10.1001/jamanetworkopen.2022.53845
|View full text |Cite
|
Sign up to set email alerts
|

Reports of Guillain-Barré Syndrome After COVID-19 Vaccination in the United States

Abstract: ImportanceBecause of historical associations between vaccines and Guillain-Barré syndrome (GBS), the condition was a prespecified adverse event of special interest for COVID-19 vaccine monitoring.ObjectiveTo evaluate GBS reports to the Vaccine Adverse Event Reporting System (VAERS) and compare reporting patterns within 21 and 42 days after vaccination with Ad26.COV2.S (Janssen), BNT162b2 (Pfizer-BioNTech), and mRNA-1273 (Moderna) COVID-19 vaccines.Design, Setting, and ParticipantsThis retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 21 publications
1
54
1
Order By: Relevance
“…Furthermore, the early diagnosis of GBS in patients with COVID-19 is considered to be important, as the clinical course and progression correlate with the severity of disease and requirement of intensive care and mechanical ventilation [ 178 ]. A recent large-scale study also found that a replication-incompetent human adenovirus vector-based COVID-19 vaccine is associated with an increased risk of GBS [ 179 ]. The exact mechanism of action is poorly understood, but it is thought that the cell-surface antigen called as angiotensin-converting enzyme 2 (ACE2) and gangliosides are responsible for the interaction and uptake of SARS-CoV-2 [ 180 , 181 ].…”
Section: Guillain–barre Syndromementioning
confidence: 99%
“…Furthermore, the early diagnosis of GBS in patients with COVID-19 is considered to be important, as the clinical course and progression correlate with the severity of disease and requirement of intensive care and mechanical ventilation [ 178 ]. A recent large-scale study also found that a replication-incompetent human adenovirus vector-based COVID-19 vaccine is associated with an increased risk of GBS [ 179 ]. The exact mechanism of action is poorly understood, but it is thought that the cell-surface antigen called as angiotensin-converting enzyme 2 (ACE2) and gangliosides are responsible for the interaction and uptake of SARS-CoV-2 [ 180 , 181 ].…”
Section: Guillain–barre Syndromementioning
confidence: 99%
“…Moreover, although GBS cases were observed in individuals vaccinated with different COVID-19 vaccines, its increased risk was only found for adenoviral vector vaccines (19,21,22,58). Therefore, European Medicine Agency included a warning of GBS in the updated versions of package information of AZD1222 and Ad26.COV2.S vaccines (59,60), but not for other COVID-19 vaccines.…”
Section: Evaluating the Hypotheses 31 Guillain-barre ́Syndrome And Sp...mentioning
confidence: 99%
“…on mRNA vaccines (e.g., nearly 1 billion doses of mRNA vaccines vs. approximately 185 million doses of adenoviral vector vaccines were given in the European Economic Area by early February 2023)(61). Therefore, if the post-vaccination GBS was related to cross-reactive anti-spike antibodies generated after immunization, it should be predominantly observed after mRNA, not adenoviral vaccination, but the evidence points to the contrary(19,21, 58). Moreover, the varying risk of GBS observed for COVID-19 vaccines cannot be explained by the difference in the prefusion stability of full-length spike protein encoded by adenoviral, and mRNA vaccines, and present in subunit protein vaccines.…”
mentioning
confidence: 99%
“…The needed terms “increase” or “increased” were missing in descriptions of OE ratios and risk of Guillain-Barré syndrome for BNT162b2 and mRNA-1273 vaccines in the Abstract, Results, and Discussion. This article has been corrected …”
mentioning
confidence: 99%
“…In the Original Investigation titled “Reports of Guillain-Barré Syndrome After COVID-19 Vaccination in the United States,” 1 published February 1, 2023, there were errors in the Results in the number of Brighton level 1 cases and the observed-to-expected (OE) ratio data for the BNT162b2 vaccine 42-day postvaccination interval. The needed terms “increase” or “increased” were missing in descriptions of OE ratios and risk of Guillain-Barré syndrome for BNT162b2 and mRNA-1273 vaccines in the Abstract, Results, and Discussion.…”
mentioning
confidence: 99%